2008
DOI: 10.1016/j.molcel.2008.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Modes of Regulation of the Uch37 Deubiquitinating Enzyme in the Proteasome and in the Ino80 Chromatin-Remodeling Complex

Abstract: SUMMARY Deubiquitinating enzymes (DUBs) are proteases that can antagonize ubiquitin-mediated signalling by disassembling ubiquitin-protein conjugates. How DUBs are regulated in vivo and how their substrate specificities are achieved are largely unknown. The conserved DUB Uch37 is found on proteasomes in organisms ranging from fission yeast to humans. Deubiquitination by Uch37 is activated by proteasomal binding, which enables Uch37 to process polyubiquitin chains. Here we show that in the nucleus Uch37 is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 31 publications
5
133
0
1
Order By: Relevance
“…Inhibition is relieved by transient interaction with the proteasome, leading to the suggestion of cooperation between these two complexes in either transcription or DNA repair, both processes to which each complex has been linked (285). POH1 DUB activity has also recently been proposed to contribute to the choreography of the double-strand break DNA repair response (31).…”
Section: A Proteasomal Dubsmentioning
confidence: 99%
“…Inhibition is relieved by transient interaction with the proteasome, leading to the suggestion of cooperation between these two complexes in either transcription or DNA repair, both processes to which each complex has been linked (285). POH1 DUB activity has also recently been proposed to contribute to the choreography of the double-strand break DNA repair response (31).…”
Section: A Proteasomal Dubsmentioning
confidence: 99%
“…Hence, USP14 and UCH37 can potentially modulate the ubiquitylation status of proteins prior to their commitment for degradation, whereas Rpn11 acts at later stages (Worden et al, 2014). Interestingly, UCH37 is also part of another complex, the chromatin-remodelling INO80 complex, in which its activity is inhibited (Yao et al, 2008). Elegant structural studies have revealed that equivalent DEUBiquitylase ADaptor (DEUBAD) domains present in both Rpn13 (also known as ADRM1 in mammals) and INO80G (also known as NFRKB) induce distinct structural rearrangements in UCH37 that result in its activation at the proteasome and inhibition at the INO80 complex, respectively (Sahtoe et al, 2015;VanderLinden et al, 2015).…”
Section: Interacting Partners Of Dubsmentioning
confidence: 99%
“…Subsequent purification of the human INO80 complex revealed that it shares with its S. cerevisiae counterpart a set of subunits including the Ino80 SNF2 ATPase, the AAA+ ATPases Tip49a and Tip49b, actin-related proteins Arp4, Arp5, and Arp8, and the Ies2 and Ies6 proteins (2,(10)(11)(12). The human INO80 complex lacks orthologs of the remaining subunits of the S. cerevisiae INO80 complex and contains instead several apparently metazoan-specific subunits including the deubiquitinating enzyme Uch37, the gene altered in glioma (GLI)-Kruppel family zinc finger transcription factor YY1, the forkhead-associated domain (FHA) containing Mcrs1, nuclear factor related to kB (Nfrkb), and the Amida, Ino80D (FLJ20309), and Ino80E (FLJ90652) proteins.…”
Section: Ino80 Complex | Enzyme Activitymentioning
confidence: 99%